Li Shutong’s Contribution to Modern Music Education in China - Zhong, Yujie (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
Since modern times, Chinese music culture and education have embarked on a historical process of transition from tradition to modernity. At the beginning of the 20th century, with the introduction of Western music and the establishment of new-style schools, pioneers of music art represented by Li Shutong made many pioneering contributions to the development of music culture in modern China through music education and music creation practice, and had a profound impact on it. Previous studies have conducted preliminary research on Li Shutong’s music education activities and contributions, but further exploration is needed in certain areas. This article takes Li Shutong’s music practice as the starting point, sorts out the music education activities related to Li Shutong since modern times, and explores Li Shutong’s contributions to the enlightenment music education of modern China.